Dynamics Modeling of the Crank-group Driving Mechanism with Clearance - Yan Weiliang; Cao Jujiang; Wang Yuqi; Wu Yao (Jixie chuandong)
The crank- group driving mechanism is a kind of under- actuated mechanism with redundant characteristics,aiming at the characteristics of mechanism,selecting continuous contact model for the joint clearance,the dynamics model of the basic structural unit- double crank mechanism with clearance is set up by the second kind Lagrange equation. Then,assume that the inertia force direction of no quality rod pointing to truss connecting rod,the derivation from the unit to the whole is carried out,and the dynamics model of the crank- group driving mechanism with clearance is established.